Beyond Access and Exposure: Implications of Sneaky Media Use for Preschoolers' Sleep Behavior. Issue 5 (16th April 2019) - Moorman, Jessica D.; Harrison, Kristen
ABSTRACT: Greater consumption of and access to screen media are known correlates of unhealthy sleep behavior in preschoolers. What remains unknown, however, is the role a child's media use plays in this association. Parents and guardians of U.S. preschoolers ( N = 278, average child age 56 months) provided information about their child's nightly duration of sleep, daily duration of nap, quantity of screen media use, sneaky media use, and the presence of a screen media device in the bedroom. We assessed four media: television, DVD/VCRs, video games, and computer/Internet. Based on rationales of sleep displacement, the forbidden fruit hypothesis, and social cognitive theory, we predicted that increased consumption of and access to media, along with sneaky media use, would predict a shorter duration of nightly sleep and longer duration of daily nap across the four screen media. In correlational analyses, a clear pattern emerged with quantity of media use, screen media in the bedroom, and sneaky media use associated with shorter nightly duration of sleep and longer duration of daily nap. In regression analyses, only weekday evening television viewing and sneaky media use predicted shorter nightly sleep duration; weekend morning and evening DVD use predicted longer naps.